In vitro anti-tuberculous study on the combination of extracts of stem-bark of Erythrina abyssinica Lam. ex DC and conventional drugs - Aber, Jacqueline; Ogwang, Patrick Engeu; Anyama, Norbert; Ajayi, Clement Olusoji (Journal of Pharmacognosy and Phytochemistry, 2019)
Background: Tuberculosis (TB) caused by Mycobacterium tuberculosis remains an important public health issue worldwide and TB patients are reported to use conventional drugs concurrently with medicinal plants. This study investigated effect of co-administration of Erythrina abyssinica stem-bark extract with Rifampicin and Isoniazid on Mycobacterium tuberculosis in vitro. Methods: The stem-bark of E. abyssinica was extracted using Methanol and Ethanol, separately. The extract, Rifampicin and Isoniazid drugs were separately reconstituted with distilled water for the experiment. Preserved strain of Tuberculosis H37RV was used with 7H11 middle brook agar. The Minimum concentrations of each extract was mixed with Minimum Inhibitory Concentrations of Rifampicin and Isoniazid and tested on strain of Tuberculosis H37RV to determine the inhibitory effect. Results: The combination of 0.06μg/ml ethanol extract with 0.01μg/ml RI gave 99.2% inhibition and the combination of 0.06μg/ml methanol extract with 0.01μg/ml RI gave 99% inhibition while the combination of 0.01μg/ml RI gave 86.2% inhibition Conclusion: The addition of Erythrina abyssinica extracts to the two conventional drugs produced antituberculous effect and thus corroborates the use of E. abyssinica with conventional drugs to treat tuberculosis patients. There is thus need to further investigate clinically the effects of the combination of the E. abyssinica extracts with the conventional anti tuberculosis drugs on patients
Keywords: Tuberculosis; Erythrina abyssinica; Mycobacterium tuberculosis; Conventional drugs